Peran Idola K-Pop Seventeen Dalam Meningkatkan Self-Esteem Dan Self-Forgiveness Pada Mahasiswi Usia Dewasa - Ayqina Mafazania (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
Confidence is an important element in the development of self-esteem and self-forgiveness. This study aims to reveal the role of K-pop idol Seventeen in the formation of self-esteem and self-forgiveness among young adult female students. This research method is a literature review or library study that involves reading and examining various journals, books, and various other published manuscripts related to the research topic in order to create an article on a particular topic or issue. Research shows that the content on Seventeen's YouTube channel can increase self-confidence and reduce levels of depression in young adult female students. We conclude that the feeling of well-being that occurs after viewing Seventeen's content can increase a person's self-confidence and subsequently foster self-esteem and self-forgiveness in young adult students. This reduces the intensity of depression and self-harm. Even suicidal thoughts can be removed.